Analytic philosophy - Kononovich, Lila; Garcia, Pablo; Films for the Humanities & Sciences (New Jersey : Film For The Humanities & Sciences, 2004)
This program scrutinizes the founding of analytic philosophy, the rise of logical positivism, the rejection of metaphysics, and the advent of linguistic philosophy through Russell's Principia Mathematica, Wittgenstein's Tractatus Logico-Philosophicus, Willard Van Orman Quine's 2Two Dogmas of Empiricism,3 the Vienna Circle's manifesto, and other seminal works. Penetrating commentary is provided by Harvard University's Hilary Putnam, Rutgers University's Colin McGinn, and USC's Scott Soames
Title from title screen
Executive producers, Chris Scherer, Camila O'Donnell
DVD Format
Keywords: Philosophy; Analysis (Philosophy); Logical positivism